Hydraulic Structures Theory and Applications - Ahsan, Amimul (IntechOpen, 2020)
Hydraulic Structures - Theory and Applications conveys a broad understanding of the fundamental mechanisms of various hydraulic structures. Emphasis is given to the analysis and design of different types of hydraulic structures. Various applications of hydraulic structure analysis are also incorporated. This book introduces advanced ideas on hydraulic structures: theory and applications to the international community. It includes five advanced and revised contributions, and covers (1) an introductory chapter on hydraulic structures, (2) the operation and maintenance of hydraulic structures, (3) a bottom discharge conduit for dams, (4) a review of methods of measuring streamflow using hydraulic structures, and (5) geotechnical engineering applied to earth-rock dams. The aim of the book is to provide a text for undergraduate and postgraduate students. Researchers, designers, and operators of hydraulic structures will find the text of interest and a stimulating up-to-date reference source.